The Comparison of Effectiveness and Mechanisms of Dry Cupping Therapy and Wet Cupping Therapy in Reducing Neck Pain Symptom in Hypertension - Setyawan, Aris; Budiyati, Gani Apriningtyas; Hardiyanti, Wa Ode Siti (Jurnal Keperawatan Respati Yogyakarta, 2020)
Hypertension is a risk factor for stroke, Myocardial infarction, and vascular dementia. Symptoms that often appear in hypertensive patients include neck pain, dizziness, and physical weakness. Some of the non-pharmacological therapies that can be used to reduce pain are dry cupping therapy (DCT) or wet cupping therapy (WCT). The purpose of this study is to compare the effects and mechanisms of WCT and DCT in reducing neck pain in hypertensive patients. This is pre-experimental research with a pre-post test approach involving 32 participants without a control group. The instrument used in this study is The Numeric Rating Scale questionnaire. The Numeric Rating Scale questionnaire is used as an instrument in this study. Data are analyzed with Shapiro-Wilk Normality Test, Parametric Paired T-test, and independent t-test. The result shows that there is a significant reduction of pain scale in participants within the DCT group with a p-value of 0.000, and also within participants in the WCT group with a p-value of 0.000. It can be concluded that both DCT and WCT methods have a similar effect on decreasing the scale of neck pain.